2014
DOI: 10.1007/s00414-013-0953-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of six IrisPlex SNPs and comparison of two eye color prediction systems in diverse Eurasia populations

Abstract: DNA-based prediction for externally visible characteristics such as eye color is already a useful tool in forensic criminal investigations. The IrisPlex system, consisting of six single nucleotide polymorphisms (SNPs) and a prediction model, was developed based on individuals from several European populations. Other recent studies have developed a different prediction model, also based on European populations. In this study, we compared two prediction models using the data for the six IrisPlex SNPs genotyped o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 27 publications
5
37
1
Order By: Relevance
“…The studies have confirmed that OCA2 gene, as well as other three genes, HERC2, SLC24A4, and SLC24A5, respectively, were discovered to have significant melanin effects in determining human iris colors by regulating melanin production and expression in the eye [1,3,8,9,12,16]. Moreover, HERC2 gene was discovered to be strongly associated with blue eye color; further analysis has presented that rs12913832 in HERC2 was responsible for determining blue and brown eye color variation [3,9,[16][17][18], and also has the highest discrimination power for predicting either light or dark iris color among various population groups [3,12].…”
Section: Introductionmentioning
confidence: 51%
See 4 more Smart Citations
“…The studies have confirmed that OCA2 gene, as well as other three genes, HERC2, SLC24A4, and SLC24A5, respectively, were discovered to have significant melanin effects in determining human iris colors by regulating melanin production and expression in the eye [1,3,8,9,12,16]. Moreover, HERC2 gene was discovered to be strongly associated with blue eye color; further analysis has presented that rs12913832 in HERC2 was responsible for determining blue and brown eye color variation [3,9,[16][17][18], and also has the highest discrimination power for predicting either light or dark iris color among various population groups [3,12].…”
Section: Introductionmentioning
confidence: 51%
“…In fact, when Yun et al [12], compared the prediction outcomes using two different methods, one being the FROG-kb used in Walsh et al [16][17][18]'s IrisPlex system and the other one being Ruiz et al [27]'s Snipper based on Bayseian form, two systems showed no contradicting predictions among East Asian samples. This finding indicates that while these platforms can be used to rule out East Asians among other population groups, these SNPs would not allow further detailed differentiation within the East Asian groups.…”
Section: Evc Research In Korea/east Asiamentioning
confidence: 99%
See 3 more Smart Citations